English grammar in use extra [ - MURPHY; Craven; Viney (Cambridge: Cambridge University Press, 2012)
Minimum system requirements for accompanying CD-ROM: PC with 233 MHx processor or faster; Windows 98, NT4, 2000, ME, or XP; CD-ROM drive; 64 MB RAM; 300 MB available hard disk space; Internet Explorer 5.0 or later; super VGA color monitor, 800x600 resolution; mouse. Sound card with speakers and microphone optional
To accompany textbook titles "English grammar in use: a self-study reference and practice book for intermediate learners of english : With answers / Raymond Murphy"
COLAL
Keywords: English language -- -- Computer-assisted instruction for foreign speakers -- -- Case studies; English language Grammar -- -- Problems, exercises, etc; English language -- -- Grammar; English language -- -- Text books for foreign speakers